Paradigma Tafsir Ilmi dalam Perspektif Mufassir Klasik dan Modern - ipin tajul (Program Studi Hukum Keluarga Islam, 2023)
The dynamics of modern science which are the pillars of civilization, greatly influence the human perspective on the universe and even on religious beliefs. The Koran as a guideline for the life of Muslims provides guidance in interacting with nature and all creatures, so that the (rational) potential of reason in elaborating Allah's verses, both Qauliyah (Koran) and Kauniyah (universe phenomena) greatly influences patterns of scientific interpretation. The emergence of scientific interpretation with a scientific approach and empirical scientific theory has long been a discourse of discussion by scholars, namely the extent to which reason or ra'yu plays a role in interpreting the Koran which is the word of God and absolute truth. The paradigm of scientific interpretation with scientific and scientific disciplines carried out by classical and modern mufaser indicates a correlation between revelation and reason and aims to prove the miracles of the Koran that are relevant to the times. This research study is library research, while for data analysis the method used is historical and descriptive-qualitative approaches with content analysis. So that from the results of this study one can understand the paradigm of scientific interpretation of classical and modern mufaser as well as the development of interpretation methods by approaching the aspects of the miracles of the Koran.